The Effect of Concentration and Time Interval of Kinetin Application on The Growth of Daun Duduk (Desmodium triquetrum L.) Seeds - Asty Pratista Magdhalena; Bambang Puji Asmanto; Sulandjari Sulandjari; Ahmad Yunus (Journal of Biodiversity and Biotechnology, 2021)
Daun duduk (Desmodium triquetrum L.) is a medicinal plant that has the power to treat hemorrhoids, but has not been widely cultivated. This research was conducted to obtain the right concentration and time interval of kinetin application to increase the growth of Daun duduk seedlings. This research was conducted from November 2019 until March 2020 at the Screen House, Faculty of Agriculture, UNS. The factors of the experiment were concentration of kinetin (0 ppm, 10 ppm, 20 ppm and 30 ppm) and the time interval of application (once every three months, once every 1.5 months and once a month). The parameters observed in this study were plant height, stem diameter, number of leaves, number of branches, number of roots, root length, fresh stover and dry stover. The results showed that the single factor of kinetin concentration could increase plant height, stem diameter, number of leaves, number of branches and dry stover. Meanwhile, the time interval for application and the interaction between the two factors did not have any significant effect. The most effective kinetin concentration in increasing the growth of Daun duduk was 30 ppm. Keywords: growth regulators; herbal medicines; plant height.